Building with Plastic. A New Possible Solution for the Environment - Daniela Besana; Claudia Ferrari (Agathón)
The research concerns a possible way for recycling plastic bottles as construction material, as an additional reuse circuit. Following a preliminary critical analysis of case studies to highlight the possible design variables, an innovative method which uses plastic bottles for the construction of load-bearing walls is proposed. Models of different constructive solutions have been designed and built, up to the proposal of a module of four bottles, filled with sand and tied together. Laboratory compression tests have shown the strength of the basic module and a f.e.m. analysis has demonstrated the stability of the structure. These first results encourage to other more accurate analysis and testify its potential versatility as building material and exportability of use even in different contexts, at a social, economic and environmental level.